Levels of Serum Nitric Oxide and Ascorbic Acid in Early Pregnant and Non-pregnant Sheep During Breeding Season - Malik, A. A.; Fazili, M. R.; Khatun, A. (International Journal of Livestock Research, 2021)
The objective of this study was to determine the levels of nitric oxide (NO) and ascorbic acid (AA) in early pregnant and non-pregnant cross bred sheep during breeding season. The cross bred ewes (n=30) were equally allotted to three groups depending upon the length of time the progesterone sponges were kept in the vagina. The groups were designated as short (6 days), medium (10 days) and long-term (14 days) treatment. All the ewes were injected PGF2α 250µg, intramuscularly 24 hours before sponge removal. After the sponge removal ewes were kept with breeding rams for tupping upto 72 hours. Blood samples were collected on different days for analysis of serum NO and AA concentration. There was progressive significant (P<0.05) increase in serum nitric oxide and ascorbic acid concentrations from day 0 to day 10, 17 and 35 of pregnancy compared to non-pregnant ewes. It was concluded that the levels of the serum nitric oxide and ascorbic acid differ between pregnant and non-pregnant ewes during early pregnancy.